Improved joint health in subjects with severe haemophilia A treated prophylactically with recombinant factor VIII Fc fusion protein - Oldenburg, J.; Kulkarni, R.; Srivastava, A.; Mahlangu, J. N.; Blanchette, V. S.; Tsao, E.; Winding, B.; Dumont, J.; Jain, N. (Haemophilia : the official journal of the World Federation of Hemophilia, 2018)
Introduction Joint arthropathy is the long‐term consequence of joint bleeding in people with severe haemophilia. Aim This study assessed change in joint health over time in subjects receiving recombinant factor VIII Fc fusion protein (rFVIIIFc) prophylaxis. Methods ALONG is the phase 3 pivotal study in which the benefit of rFVIIIFc as a prophylactic treatment for bleeding control was shown in previously treated severe haemophilia patients ≥12 years of age (arm 1: 25‐65 IU/kg every 3‐5 days, arm 2: 65 IU/kg weekly and arm 3: episodic). After completing ALONG, subjects had the option to enrol into the extension study (ASPIRE). This interim, post hoc analysis assessed changes in joint health over ~2.8 years in these patients. Results Forty‐seven subjects had modified Haemophilia Joint Health Score (mHJHS) data at A‐LONG baseline, ASPIRE baseline and ASPIRE Year 1 and Year 2. Compared with A‐LONG baseline (23.4), mean improvement at ASPIRE Year 2 was −4.1 (95% confidence interval [CI], −6.5, −1.8; P = .001). Regardless of prestudy treatment regimen, subjects showed continuous improvement in mHJHS from A‐LONG baseline through ASPIRE Year 2 (prestudy prophylaxis: −2.4, P = .09; prestudy episodic treatment: −7.2, P = .003). Benefits were seen in subjects with target joints (−5.6, P = .005) as well as those with severe arthropathy (−8.8, P = .02). The mHJHS components with the greatest improvement at ASPIRE Year 2 were swelling (−1.4, P = .008), range of motion (−1.1, P = .03) and strength (−0.8, P = .04). Conclusions Prophylaxis with rFVIIIFc may improve joint health over time regardless of prestudy prophylaxis or episodic treatment regimens.